2005
DOI: 10.1238/physica.regular.072a00cc1
|View full text |Cite
|
Sign up to set email alerts
|

4p States and X-Ray Spectroscopy

Abstract: Novel integrable systems of coupled first-order autonomous PDEs in 1 + 1 dimensions (space x and time t) are presented. Integrable covariant 2-vector and 3-vector PDEs, as well as higher-order integrable PDEs for a single, or a couple, of scalar-dependent variables (including an extension of the sine-Gordon equation and a remarkably neat, highly nonlinear third-order PDE), are also obtained by appropriate reductions of the basic matrix equations. The Lax pairs that characterize the integrable character of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Actually, for most of transition-metal compounds, both experimental studies and theoretical studies based on electronic structure calculations have revealed that the RXS intensities are brought about by the hybridization between the 4p band and the 2p band of the neighboring anions rather than the direct Coulomb interaction between the electron in the 4p band and electrons in the 3d band. 3,4 This result is reasonable because of the extended nature of the 4p state.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Actually, for most of transition-metal compounds, both experimental studies and theoretical studies based on electronic structure calculations have revealed that the RXS intensities are brought about by the hybridization between the 4p band and the 2p band of the neighboring anions rather than the direct Coulomb interaction between the electron in the 4p band and electrons in the 3d band. 3,4 This result is reasonable because of the extended nature of the 4p state.…”
Section: Introductionmentioning
confidence: 55%
“…We have demonstrated the usefulness of the derived formula by calculating the E2 RXS spectra in Ce 1−x La x B 6 . Phase II is believed to be an AFQ order of O xy type, and our formula dictates that the energy dependence is given by a combination of α (2) E2 (ω) and α (4) E2 (ω). We have obtained the RXS intensity in the same order of intensity as obtained by assuming the AFO order.…”
Section: Discussionmentioning
confidence: 98%
“…It is well known that the radiative decay of atoms ionized to different degrees in the inner and outer shells gives rise to a complex x-ray spectrum consisting of a large number of closely spaced fine structure lines and the complexities of the x-ray spectrum depend on the initial multiple vacancy states and also on the numerous possible transitions. The studies for atomic x-ray spectra [1,2] as well as molecular x-ray spectra [3][4][5] have attracted much interest in recent years. Spin-forbidden electric dipole transitions are of great importance as diagnostics for different astrophysical sources, laboratory-induced fusion plasmas and also in the study of atomic collisions [6].…”
Section: Introductionmentioning
confidence: 99%